Bronchial Asthma: A Chronic Respiratory Condition (Open Academia: Journal of Scholarly Research, 2026)
This research paper explores bronchial asthma, a chronic inflammatory disease of the respiratory system that affects millions of people worldwide. The paper discusses the causes, risk factors, symptoms, types, diagnosis, treatment, and prevention of asthma. Special attention is given to environmental triggers, genetic predisposition, and modern treatment methods, including medications and lifestyle modifications. The paper emphasizes the importance of early diagnosis and proper management to improve patients’ quality of life and prevent severe complications. The study concludes that asthma, despite being incurable, can be effectively controlled with medical treatment and preventive measures.